Malicious Obstruction of Religious Acts in Light of the Provisions of the Penal Code - Majchrzak, Katarzyna (Prawo Kanoniczne, 2025)
The article presents an analysis of the criminal offense of maliciously obstructing the public performance of religious acts, funeral ceremonies, or mourning rites. The discussion primarily focuses on the legal interest protected by this provision, the characteristics of the perpetrator, and the objective elements of the offense. Any individual capable of bearing criminal responsibility may be deemed the perpetrator. Particular attention is given to the perpetrator’s intent and malicious motivation, which constitute key elements of this offense.